Agony of the unknown heritage: Timeless synergy of the old Agricultural Bank of Chiclayo - Chafloque Pinedo, Luisa Enith (2022)
The objective of the present investigation was to understand the values of the ignored heritage Old Agricultural Bank in the city of Chiclayo, from the paradigm of the timeless synergy, understanding the limited communication, the altered bond and the corrupted architecture, generated by the contemporary society. The survival of the unknown proposes values clearly affected by the patrimonial subjects. This research is qualitative, critical and propositive, seeking the understanding of the causes - effects and deficiencies - consequences of the ignored behavior affecting the values of the patrimonial subjects. The final findings concluded that the most affected heritage values are educational, use and economic, proposing twelve intervention strategies regarding the components of the timeless synergy: cybernetics, quaternary and heritage holography, thus improving the values of the ignored heritage.